On application of Combined Pile-Raft Foundations for road structures - Leppla, Steffen; Norkus, Arnoldas (International Conference “Environmental Engineering”, 2020)
Roads and road infrastructure systems are designed to satisfy ultimate and serviceability conditions under long-term actions caused by transport loadings and environmental effects. Selected design solutions must be safe and rational in terms of construction and maintenance costs. In cases when weak or soft soil layers of natural soil profiles are shallow and/or the traffic loads are very large, the Combined Pile-Raft Foundation (CPRF) is the economical road and railway structure design solution. Application of CPRF is cheaper geotechnical solution comparing with soil change or usual piled foundation alternatives. The development of this system is based on the analysis of relevant mechanical properties of soil layers and the evaluation of the soil-structure interaction. The soil-structure interaction is of highest importance allowing proper evaluation of load bearing resistance and deformation transmitted by raft and piles to soil layers. The soil and foundation system usually is subjected by loadings, resulting elastic-plastic resistance range. Therefore, relevant nonlinear physical laws due to the stress levels are used. The paper purpose is summarizing the experience of application of Combined Pile-Raft Foundations used in road and railway construction and bridge engineering.
Keywords: road structure; soil-structure interaction; Combined Pile-Raft Foundations; performance analysis